2015
DOI: 10.5194/bgd-12-11019-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coastal upwelling off Peru and Mauritania inferred from helium isotope disequilibrium

Abstract: Abstract. Oceanic upwelling velocities are too small to be measured directly. The surface disequilibrium of the 3He/4He ratio provides an indirect method to infer vertical velocities at the base of the mixed layer. Samples of helium isotopes were taken from two coastal upwelling regions, off Peru on cruise M91, and off Mauritania on 3 cruises. The helium-3 flux into the mixed layer also depends on the diapycnal mixing. Direct observations of the vertical diffusivity have been performed on all 4 cruises and are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The vertical advective flux by Ekman divergence requires determination of vertical velocity in the water column that varies with depth and distance from the coastline. Convincing agreement between vertical velocities derived from Ekman divergence following Gill (1982) determined from scatterometer winds and from helium isotope disequilibrium I. Rapp et al: Controls on redox-sensitive trace metals in the Mauritanian oxygen minimum zone within the Mauritanian and Peruvian coastal upwelling regions was found by Steinfeldt et al (2015) (see their Fig. 4).…”
Section: Turbulence Measurements and Vertical Flux Calculationsmentioning
confidence: 71%
See 2 more Smart Citations
“…The vertical advective flux by Ekman divergence requires determination of vertical velocity in the water column that varies with depth and distance from the coastline. Convincing agreement between vertical velocities derived from Ekman divergence following Gill (1982) determined from scatterometer winds and from helium isotope disequilibrium I. Rapp et al: Controls on redox-sensitive trace metals in the Mauritanian oxygen minimum zone within the Mauritanian and Peruvian coastal upwelling regions was found by Steinfeldt et al (2015) (see their Fig. 4).…”
Section: Turbulence Measurements and Vertical Flux Calculationsmentioning
confidence: 71%
“…1: right term, right-hand side) were estimated. On the continental margin below the surface mixed layer, solutes are transferred vertically toward the near-surface layers by turbulent mixing processes and by vertical advection forced by Ekman divergence (e.g., Kock et al, 2012;Milne et al, 2017;Rhein et al, 2010;Steinfeldt et al, 2015;Tanhua and Liu, 2015):…”
Section: Turbulence Measurements and Vertical Flux Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In EBUSs, besides horizontal advection of nutrients from the CZ to the CTZ by mesoscale and submesoscale features, diapycnal mixing has been identified as an important mechanism of vertical mixing in the CTZ. This is especially so at the continental margin, contributing to vertical injections of gases, solutes, and organic matter toward the upper layer (Callbeck et al, ; Li et al, ; Loginova et al, ; Steinfeldt et al, ). The effects of diapycnal mixing on phytoplankton community size distribution in EBUSs based on observational data remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown ecological changes in EBUS ecosystem structure (Fréon et al, 2009;Wang et al, 2015), hence monitoring these systems is becoming increasingly important. EBUS are formed in part by wind-driven ocean circulation, and their upwelling is dependent on wind direction and strength (Capet et al, 2004;Messié and Chavez, 2015;Steinfeldt et al, 2015). Recognizing that alongshore winds that drive upwelling are initiated by changes in atmospheric pressure gradients at the cross-shore, Bakun (1990) hypothesized that long-term changes in climatic conditions would likely intensify continental oceanic pressure gradients (Bakun, 1990;García-Reyes et al, 2015) and subsequently result in an increase in the frequencies and intensities of upwelling-favorable winds.…”
Section: Introductionmentioning
confidence: 99%